Downward accountability mechanism effectiveness by non-governmental organizations in low- and middle-income countries: A qualitative systematic review - Elizabeth Noble; Dina Moinul; Oumou Khairy Djim Sylla; Sophia Friedmann; Kristen Amick; Nehal Rowhani; Rashi Dua; Nowshin Mannan; Cathleen Seaman; Omobolanle Ayo; Shubhra Pant; Oluwatimilehin Osoko; et al. (PLoS ONE, 2025)
Background Downward accountability, defined as being answerable to beneficiaries for actions and giving affected populations influence in aid processes, remains unstandardized and underinvested across the humanitarian sector. Currently, numerous accountability mechanisms are being utilized by humanitarian non-governmental organizations (NGOs) in low- and middle-income countries (LMICs). However, the different mechanisms have varying degrees of effectiveness in providing true accountability to affected populations due to significant barriers or strengths in implementation. Objective To conduct a qualitative systematic review investigating the various downward accountability mechanisms employed by non-governmental organizations in LMICs, and to assess the effectiveness of these mechanisms in delivering downward accountability for populations in low-resource settings. Results We searched 10 databases, including PubMed, Medline, Embase, Ovid, Web of Science, Global Health, EBSCO SocINDEX, ABI/INFORM, ALNAP, and Sociological Abstracts from 2008–2023. Grey literature was searched on Google Scholar. To capture any additional articles, the search was updated in November 2024. Our search produced 1521 articles. After applying our exclusion criteria and screening, 38 articles comprised our final dataset. Each article reported on the effectiveness of five downward accountability mechanisms, including participation, ownership, transparency, program auditing, and social auditing. Associated barriers to accountability included implementation, power asymmetry, and fragmentation within the humanitarian sector. Conclusions There are significant gaps in research on the effectiveness of downward accountability mechanisms amongst humanitarian NGOs in LMICs. This research deficit adversely affects the sustainability of local development initiatives and, on a broader scale, undermines overall organizational effectiveness. Implementing balanced accountability mechanisms that promote equality in power dynamics is pivotal to achieving meaningful outcomes for affected populations.